Neutralization of Malaria Glycosylphosphatidylinositol In Vitro by Serum IgG from Malaria-Exposed Individuals - de Souza, J. Brian (American Society for Microbiology (ASM), 2010)
Parasite-derived glycosylphosphatidylinositol (GPI) is believed to be a major inducer of the pathways leading to pathology and morbidity during Plasmodium falciparum infection and has been termed a malaria “toxin.” The generation of neutralizing anti-GPI (“antitoxic”) antibodies has therefore been hypothesized to be an important step in the acquisition of antidisease immunity to malaria; however, to date the GPI-neutralizing capacity of antibodies induced during natural Plasmodium falciparum infection has not been evaluated. Here we describe the development of an in vitro macrophage-based assay to assess the neutralizing capacity of malarial GPI-specific IgG. We demonstrate that IgG from Plasmodium falciparum-exposed individuals can significantly inhibit the GPI-induced activation of macrophages in vitro, as shown by reduced levels of tumor necrosis factor production and attenuation of CD40 expression. The GPI-neutralizing capacity of individual IgG samples was directly correlated with the anti-GPI antibody titer. IgG from malaria-exposed individuals also neutralized the macrophage-activating effects of P. falciparum schizont extract (PfSE), but there was only a poor correlation between PfSE-neutralizing activity and the anti-GPI antibody titer, suggesting that PfSE contains other macrophage-activating moieties, in addition to GPI. In conclusion, we have established an in vitro assay to test the toxin-neutralizing activities of antimalarial antibodies and have shown that anti-GPI antibodies from malaria-immune individuals are able to neutralize GPI-induced macrophage activation; however, the clinical relevance of anti-GPI antibodies remains to be proven, given that malarial schizonts contain other proinflammatory moieties, in addition to GPI.